Smoking Cessation Among Methadone-Maintained Patients: A Meta-Analysis - Yee, Anne; Hoong, Moey Chee; Joyce, Yong Chen; Loh, Huai Seng (Taylor & Francis, 2018)
Background: Nicotine use disorder is highly prevalent among methadone maintenance patients with its tobacco-related problems. However, the treatment modalities for nicotine use disorder remain limited. Objective: Our meta-analysis aims to examine the effectiveness of smoking cessation treatment in this group of patients. Methods: A total of 1358 participants were recruited from 9 eligible studies, published from the start of studies in this field till Feb 2016, identified from PubMed, OVID, EMBASE and Google Scholar databases. Two independent reviewers assessed the eligibility of each report based on predefined inclusion criteria. Pooled odd ratios or weighted mean difference was performed using random effects. Results: The treatments for smoking cessation among MMT patients are behavioral and pharmacological therapies. Smoking cessation was better achieved with nicotine replacement therapy (NRT) especially with adjunctive behavioral therapy. The pooled odds ratio of smokers’ abstinence of smoking by the end of the treatment between NRT and placebo group was 6.32 (95% CI = 1.18 to 33.75, p = 0.03) and is statistically significant. Any additional behavior therapy among MMT patients who received the smoking cessation pharmacotherapy as the primary treatment was not better than those who only received standard care (Odds ratio was 2.53, 95% CI = 0.75 to 8.56, p = 0.14). Conclusions: Although NRT is proven to be effective in smoking cessation, more studies are warranted to prove the effects of other pharmacotherapy in smoking cessation.